2001
DOI: 10.1002/bit.10058
|View full text |Cite
|
Sign up to set email alerts
|

On‐line stoichiometry and identification of metabolic state under dynamic process conditions

Abstract: A method for the on-line calculation of conversion rates and yield coefficients under dynamic process conditions was developed. The method is based on cumulated mass balances using a moving average method. Elemental balances were used to test the measured cumulated quantities for gross errors and inappropriate stoichiometry definition followed by data reconciliation and estimation of non-measured conversion rates, using a bioprocess set-up including multiple on-line analysis techniques. The quantitative potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
72
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(73 citation statements)
references
References 26 publications
1
72
0
Order By: Relevance
“…The cumulative carbon balance, in Cmol per Cmol of biomass (Cmol Cmol x Ϫ1 ), compares the cumulative uptake of carbon sources with the accumulation of known carbon sinks, calculated at each sampling time point relative to time zero, when the glucose pulse was given (14). During the postpulse period, glucose (added via both the pulse and the feed) was the sole carbon source, assuming that the small amount of ethanol in the feed was not metabolized.…”
Section: Vol 72 2006 Metabolome Dynamics and Balances In S Cerevismentioning
confidence: 99%
See 1 more Smart Citation
“…The cumulative carbon balance, in Cmol per Cmol of biomass (Cmol Cmol x Ϫ1 ), compares the cumulative uptake of carbon sources with the accumulation of known carbon sinks, calculated at each sampling time point relative to time zero, when the glucose pulse was given (14). During the postpulse period, glucose (added via both the pulse and the feed) was the sole carbon source, assuming that the small amount of ethanol in the feed was not metabolized.…”
Section: Vol 72 2006 Metabolome Dynamics and Balances In S Cerevismentioning
confidence: 99%
“…Under quasi-steady-state conditions, for example, material balances of extracellular metabolites are required for metabolic flux analysis (33). Previous work has evaluated dynamic carbon balances in a time frame of tens of minutes to hours (14,26,45), based on measured extracellular fluxes and an assumed intracellular quasi-steady state. Under dynamic conditions and within the time frame of interest for in vivo kinetic analysis, setting up material balances requires comprehensive quantification of extra-and intracellular metabolite concentrations as well as the in vivo O 2 uptake rate and CO 2 evolution rate.…”
mentioning
confidence: 99%
“…The A-stat approach has also been used for m crit screening in a study of an enological yeast strain, Saccharomyces uvarum, used in wine production, which led to a purely oxidative fed-batch process (Albergaria et al, 2000) and in a study of S. cerevisiae for the development of a mathematical model enabling the quantitative description of transient changes in metabolism (Herwig et al, 2001). Two studies have investigated the effects of cultivation medium composition on m crit of S. cerevisiae: whilst one study concluded that supplementing glucose-based mineral medium with ethanol had no effect on m crit (Paalme et al, 1997a), the other study showed an 8 % increase of m crit on medium supplemented with oleic acid (Marc et al, 2013).…”
Section: Main Results Referencementioning
confidence: 99%
“…One approach is to approximate the derivative de/dt with a simple method, such as Euler or Runge-Kutta methods, and then solve (2) (Herwig, 2001). Euler methods provide the most straightforward approximations:…”
Section: Euler Approximation and Moving Average Filtersmentioning
confidence: 99%
“…Thus, the new signal becomes smoother. This kind of filters has already been applied to the calculation of metabolic fluxes (Herwig, 2001). …”
Section: Euler Approximation and Moving Average Filtersmentioning
confidence: 99%